Dampak pengelolaan manajemen risiko finansial terhadap kinerja dan nilai perusahaan perbankan - Putri, Nurul Fajriyah Hidayat (Maliki Interdisciplinary Journal, 2024)
This research aims to find out whether good financial management has an impact on the value of a company in the future considering that company value is a very important representation of measuring the level of company health. This research is scientific research with research sources in the form of literature review. The results of this research review are that good financial management will also have a positive impact on company performance and value. This can be realized through effective use of resources and management of other risks.